Analisis Faktor – Faktor Yang Mempengaruhi Opini Audit Going Concern Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Tahun 2017-2020 - Natasya Tarida Theresia Br Sihaloho; Natalie Beatrice Tarigan; Mega Yenty; Saung Hwee Teng; Hantono Hantono (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The Indonesia Stock Exchange (IDX) has explained that there are still a number of companies whose businesses have been discontinued, which still need to be questioned or reviewed. This is because not all issuers listed on the Indonesia Stock Exchange have canceled their prospective future business (kelangsungan hidups). One of the criteria for a company that is said to have no theft attempts is if the company has no income or continuous loss performance. In order to collect data that is used as a support in this discussion, the authors use data collection methods, namely: Documentation method is a method used as a basis for analyzing data in this study by collecting data, how to record, collect and study company data related to financial reports published on the official website www.idx.co.id. Based on the results of the analysis and discussion regarding the influence of Profitability, Previous Years' Pemeriksaan Pendapatanons and Company Size on Kelangsungan hidup Pemeriksaan Pendapatanons in Manufacturing Companies Registered on the IDX in 2017-2019, it can be concluded as follows: Based on the calculation results obtained tcount > ttable, namely 1,188 > 1 .98472 and a sig value of 0.038 > 0.05, then H1 is rejected and H0 is accepted. So it can be concluded that profitability has no positive effect on kelangsungan hidup pendapatanon. Based on the calculation results, tcount > ttable is 2.109 > 1.98472 and a sig value of 0.04 <0.05, then H2 is accepted and H0 is rejected. So it can be concluded that the previous pemeriksaan pendapatanon had a positive effect on kelangsungan hidup pendapatanon. Based on the calculation results, tcount > ttable is 3.492 > 1.98472 and a sig value of 0.02 <0.05, then H2 is accepted and H0 is rejected. So it can be concluded that company size has a positive effect on kelangsungan hidup pendapatanon. Based on the calculation results, tcount > ttable is 3.287 > 1.98472 and a sig value of 0.01 <0.05, then H2 is accepted and H0 is rejected. So it can be concluded that profitability, previous pemeriksaan pendapatanon and company size have a positive effect on kelangsungan hidup pendapatanon. Keywords: Profitability, Previous Year's Opinion, Company Size, Going Concern Opinion